2006
DOI: 10.3171/spi.2006.5.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow up of surgical outcomes in patients with cervical disorders undergoing hemodialysis

Abstract: Object As increasing numbers of patients receive long-term hemodialysis, the number of reports regarding hemodialysis-related cervical spine disorders has also increased. However, there have been few reports summarizing the surgical results in patients with these disorders. The objective of this study was to evaluate the long-term follow up and clinical results after surgical treatment of cervical disorders in patients undergoing hemodialysis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 19 publications
(23 reference statements)
2
22
1
Order By: Relevance
“…First, surgical indication has been expanded to complex deformities and instabilities as well as patients with DSA and RA complicated by substantial bone fragility. 12,18,26,28,29 Consequently, the incidence in our current practice may well be higher than the value reported in previous literature. Incidentally, incidence of patients without poor bone quality such as either RA or DSA was 2.6%, which corresponds to the value reported in previous studies.…”
Section: Previous Studies On Intraoperative Lateral Mass Fracturecontrasting
confidence: 53%
“…First, surgical indication has been expanded to complex deformities and instabilities as well as patients with DSA and RA complicated by substantial bone fragility. 12,18,26,28,29 Consequently, the incidence in our current practice may well be higher than the value reported in previous literature. Incidentally, incidence of patients without poor bone quality such as either RA or DSA was 2.6%, which corresponds to the value reported in previous studies.…”
Section: Previous Studies On Intraoperative Lateral Mass Fracturecontrasting
confidence: 53%
“…Due to the biomechanical superiority of the PS system in spinal reconstruction surgery, it has been used for patients with cervical deformities or unstable pathological conditions such as acute traumatic lesions, subaxial lesions of RA, destructive spondyloarthropathy due to long-term hemodialysis and tumor metastasis to the cervical spine [1][2][3][4][5]. Recent clinical applications of the PS system include correction of kyphotic deformity in the cervical spine and occipitocervical reconstruction to correct malalignment in the craniocervical junction caused by various pathological conditions [14].…”
Section: Discussionmentioning
confidence: 99%
“…There have been increasing reports of posterior instrumentation surgery with cervical pedicle screws (PSs) for reconstruction of the cervical spine with various pathologies [1][2][3][4][5]. Despite the biomechanical superiority of cervical PSs [6], placement of cervical PSs inherits considerable risks of injuries either to nerves or to vertebral artery.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that some of the factors [5] promoting the progression of degenerative changes of the cervical spine were excessive load on the spine [6,19], a past history of lumbar vertebral diseases [17], smoking [12], and hemodialysis [20,25,27]. Jumah et al [19] investigated the factors promoting degeneration of the cervical spine in 305 Ghanans and found that 63.6% of the subjects who routinely carried baggage on their head had spondylotic changes of the cervical spine, while only 36.0% of those who did not habitually carry loads showed such changes.…”
Section: Discussionmentioning
confidence: 99%